Island of the Blue Dolphins - O'Dell, Scott 1898-1989. (Boston Houghton Mifflin, 1960)
Records the courage and self-reliance of an Indian girl who lived alone for eighteen years on an isolated island off the California coast.
Newbery Medal Award.
Keywords: Indians of North America -- Fiction; Survival -- Fiction; Islands -- Fiction; Large type books